An Energy- Efficient Routing Protocols For Wireless Sensor Network - Sandhya Vats (International Journal of Advanced Science and Technology, 2020)
There has been plenty of interest in building and deploying sensor networks. Wireless sensor network is a collection of a large number of small nodes which acts as routers also. These nodes carry very limited power source which is non-rechargeable and non-replaceable which makes energy consumption an significant issue. Energy conservation is a very important issue for prolonging the lifetime of the network. As the sensor nodes act like routers as well, the determination of routing technique plays a key role in controlling the consumption of energy. This paper describes the framework of wireless sensor network and the analysis and study of various research work related to Energy Efficient Routing in Wireless Sensor Networks.